TINJAUAN YURIDIS PERLINDUNGAN HAK-HAK NORMATIF TENAGA KERJA SETELAH BERLAKUNYA UNDANG-UNDANG CIPTA KERJA (OMNIBUS LAW) - Zubi, Muhammad; Marzuki, Marzuki; Affan, Ibnu (Jurnal Ilmiah METADATA, 2021)
The Job Creation Law, entitled Omnibus Law, is one of the government's progressive steps in the field of law. The aim of the Omnibus Law is to eliminate the overlap between laws and regulations, both in the same sector or those that are contradictory to each other and then reorganize. The formulation of the problem in this thesis is how to regulate the normative rights of workers in the Omnibus Law, how the weaknesses and strengths of the Omnibus Law in regulating the normative rights of workers compared to the Law -Law Number 13 of 2003, how to protect the law on the normative rights of workers in the Work Creation Act (Omnibus Law). The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the regulation of labor normative rights in the Work Creation Law (Omnibus Law) is the protection of workers / laborers regulated in Article 80 which regulates the strengthening of protection for workers and increases the role and welfare of workers in supporting the investment ecosystem. The weakness of the Omnibus Law in regulating the normative rights of workers compared to Law Number 13 of 2003 is that the Job Creation Law is very detrimental to workers / laborers. Legal protection of the normative rights of workers in the Omnibus Law related to the articles governing Manpower which are summarized in Article 81 has not yet accommodated guarantees of rights for workers. Guarantee of workers' rights, which in principle should have guaranteed legal protection, but if it is related to the issues raised in Law Number 11 of 2020 concerning Job Creation.